Understanding Consumer Behavior: How Attitudes, Social Norms, and Perceived Control Shape Purchase Intentions on Tokopedia - Putra, Dewa Putu Gede Wiyata; Wijaya, Bagus Kusuma (Global Researcher Network, 2024)
This study aims to analyze the influence of Attitude, Social Norms, and Perceived Behavioral Control on Purchase Intention on the Tokopedia e-commerce platform, focusing on generation Z consumers in Bali and East Java. The problem faced is the lack of understanding of psychological and social factors that influence consumer purchase intention in e-commerce. This study uses a quantitative approach with a survey method, where data is collected through questionnaires filled out by 93 respondents. Data analysis was carried out using SPSS with multiple linear regression techniques to test the effect of independent variables on dependent variables. The results showed that Attitude, Social Norms, and Perceived Behavioral Control have a significant positive effect on Purchase Intention. Among the three variables, Perceived Behavioral Control shows the greatest influence on purchase intention, followed by Attitude and Social Norms. These findings provide important insights for Tokopedia managers in designing marketing strategies barbarslot that can improve user experience and consumer purchase intention. This study also contributes to the development of the Theory of Planned Behavior in the context of e-commerce in Indonesia.